2013
DOI: 10.1038/msb.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

SH3 interactome conserves general function over specific form

Abstract: The Caenorhabditis elegans SH3 domain interactome was mapped and compared with the yeast SH3 interactome. Orthologous SH3 domain-mediated interactions are highly rewired, but the general function of the SH3 domain network is conserved between the two species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 93 publications
4
76
0
Order By: Relevance
“…Rab7 interacts with Vps34 in mammalian cells (Stein et al, 2003), and thus, it is possible that RAB-5 and/or RAB-7 regulate TBC-2 localization via recruitment of VPS-34 during early to late endosome maturation. In C. elegans, RAB-10, AMPH-1 (amphiphysin) and CED-10 (Rac1) bind to TBC-2 and regulate its localization in the recycling pathway (Liu and Grant, 2015;Sasidharan et al, 2012;Xin et al, 2013;Sun et al, 2012). However, neither rab-10, amph-1 nor ced-10 mutants have been reported to display phenotypes that would be consistent with regulating early to late endosome trafficking with TBC-2 and VPS-34.…”
Section: Discussionmentioning
confidence: 99%
“…Rab7 interacts with Vps34 in mammalian cells (Stein et al, 2003), and thus, it is possible that RAB-5 and/or RAB-7 regulate TBC-2 localization via recruitment of VPS-34 during early to late endosome maturation. In C. elegans, RAB-10, AMPH-1 (amphiphysin) and CED-10 (Rac1) bind to TBC-2 and regulate its localization in the recycling pathway (Liu and Grant, 2015;Sasidharan et al, 2012;Xin et al, 2013;Sun et al, 2012). However, neither rab-10, amph-1 nor ced-10 mutants have been reported to display phenotypes that would be consistent with regulating early to late endosome trafficking with TBC-2 and VPS-34.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that mammalian TOCA-1 coimmunoprecipitates with mammalian ABI-1 in HeLa cells (31). Interestingly, recently published yeast two-hybrid and phage display analysis of the C. elegans SH3-ome identified another component of the WAVE complex, WVE-1/Wave1, as a high-probability TOCA-1-binding protein (37). Using a GST-pull-down assay, we found that the SH3 domains of TOCA-1 and TOCA-2 bound to WVE-1, whereas the W585K mutation in the TOCA-2 SH3 domain abrogated such binding ( Fig.…”
Section: Cdc-42 and Anterior Par Complex Proteins Are Required For MImentioning
confidence: 99%
“…TOE-2 is distantly related to vertebrate proteins that contain a GAP domain in addition to their DEP domain (Arur et al, 2009). Although TOE-2 lacks a GAP domain, it can bind to the worm ortholog of GRAF, which contains a RhoGAP domain (Xin et al, 2009(Xin et al, , 2013. It is not known whether this interaction is relevant in the context of the Q.p lineage, but it suggests that TOE-2 might regulate Rho-family GTPases.…”
Section: Toe-2 Localizes Dynamically During the Divisions Of Q And Qpmentioning
confidence: 99%